Pengaruh Sistem Perpajakan, Keadilan, dan Teknologi Terhadap Persepsi Wajib Pajak Orang Pribadi Atas Perilaku Penggelapan Pajak Pada Kantor Pelayanan Pajak Pratama Pekanbaru Tampan - Pratiwi, Nadila Eka; Mirna, Yolanda; Monika, Resti Dea; Fionasari, Dwi (Yayasan Jompa Research and Development, 2024)
The purpose of this research is to determine the influence of the tax system, justice and tax technology on individual taxpayers' perceptions of tax evasion behavior at KPP Pratama Pekanbaru Tampan. The population in this study are individual taxpayers registered at KPP Pratama Pekanbaru Tampan. The number of research samples was determined using the Slovin formula, so that the sample size was 100. This research used primary data in the form of a questionnaire. The analytical method carried out in this research is multiple linear regression analysis using the SPSS version 26 program. The results of the research can prove that tax fairness, the tax system and technology can influence tax evasion at KPP Pratama Pekanbaru Tampan.